Feasibility and long-term effectiveness of a non-apical Micra pacemaker implantation in a referral centre for lead extraction. Issue 1 (8th June 2018) - Bongiorni, Maria Grazia; Della Tommasina, Veronica; Barletta, Valentina; Di Cori, Andrea; Rogani, Sara; Viani, Stefano; Segreti, Luca; Paperini, Luca; Soldati, Ezio; De Lucia, Raffaele; Zucchelli, Giulio
Abstract: Aims: To demonstrate the feasibility and long-term performances of a non-apical Micra pacemaker implantation. Methods and results: Fifty-two consecutive patients underwent Micra implantation, targeting a non-apical site of delivery when feasible. Each patient received a regular follow-up (mean 13 ± 9 months). The first 17 patients were also enrolled in the Micra transcatheter pacing system trial (Group 1); the remaining ones presented broader indications and included post-extraction subjects (Group 2). In 19 of 52 patients (Group 1: 6%, Group 2: 51%; P = 0.002) Micra was implanted because of high-risk characteristics that discouraged the implantation of a traditional pacemaker. In 31 of 52 patients (60%) Micra was implanted in a non-apical location, with a lower rate of single delivery compared with apical sites (48% vs. 81%, P = 0.035), but without any impact on electrical performance. Pacing threshold remained optimal in the majority of patients (94%), regardless of the site of implantation (apical vs. non-apical location: 0.50 vs. 0.52 V/0.24 ms; P = 0.856) and group membership, with only 6% of the subjects showing elevated values (mean 1.92 ± 0.92 V/0.24 ms) at the last follow-up. No device-related adverse events were registered. Conclusion: Micra pacemaker implant is a safe and effective procedure even in a real life cohort of high-risk patients. A non-apical site of implantation is feasible in the majority of patients allowing stable electrical performance at long-term follow-up.